High Expression of MicroRNA-196a Indicates Poor Prognosis in Resected Pancreatic Neuroendocrine Tumor. Issue 50 (December 2015) - Lee, Yoon Suk; Kim, Haeryoung; Kim, Hyoung Woo; Lee, Jong-Chan; Paik, Kyu-Hyun; Kang, Jingu; Kim, Jaihwan; Yoon, Yoo-Seok; Han, Ho-Seong; Sohn, Insuk; Cho, Jeonghee; Hwang, Jin-Hyeok
Abstract : Abstract: There is limited data on miRNA expression in pancreatic neuroendocrine tumors (PanNETs). In this study, we aimed to identify miRNAs that could be potential prognostic biomarkers of PanNETs in patients who underwent curative surgery. For miRNA target screening, 2 primary PanNETs and corresponding liver metastases were screened for miRNA expression by the NanoString nCounter analysis. Candidate miRNAs were selected by ≥2-fold difference of expression between metastatic versus primary tumor. For miRNA target validation, quantitative real-time PCR was performed for candidate miRNAs on 37 PanNETs and matched nonneoplastic pancreata, and the miRNA levels were correlated with the clinicopathological features and patient survival data. Eight miRNAs (miRNA-27b, -122, -142–5p, -196a, -223, -590–5p, -630, and -944) were selected as candidate miRNAs. Only miR-196a level was significantly associated with stage, and mitotic count. When PanNETs were stratified into high (n = 10) and low (n = 27) miRNA-196a expression groups, miRNA-196a-high PanNETs were significantly associated with advanced pathologic T stage (50.0% vs 7.4%), N stage (50.0% vs 3.7%), higher mitotic counts (60.0% vs 3.7%), and higher Ki-67-labeling indices (60.0% vs 22.2%). In addition, high miRNA-196a expression was significantly associated with decreased overall survival ( P = 0.046) and disease-free survival ( P < 0.001) during a median follow-up of 37.9 months with the hazard ratio for recurrence of 16.267 (95% confidence interval = 1.732–153.789; P = 0.015). MiRNA-196a level may be a promising prognostic marker of recurrence in resected PanNETs, although further experimental investigation would be required. Abstract : Supplemental Digital Content is available in the text